The Influence of Organizational Culture on Teacher Performance at SMK Negeri 1 Bungoro - Muh. Nasrullah; Arwansyah; Sirajuddin Saleh (ASHA Publishing, 2024)
The success of the school does not only come from the leadership but all those involved, including all teachers, staff and student cooperation who are willing to follow all the rules that apply in the school. This study is a quantitative descriptive research that aims to find out how the picture of organizational culture at SMK Negeri 1 Bungoro, to find out how the performance of teachers at SMK Negeri 1 Bungoro Pangkep Regency, and to find out how much influence organizational culture has on teacher performance at SMK Negeri 1 Bungoro. The population in this study amounted to 35 people. Data collection is carried out by observation, questionnaire, and documentation techniques. Data was obtained from research results processed using data analysis and using the SPSS 25 application consisting of Validity and Reliability Tests. Descriptive data analysis techniques and inferential statistical analysis. The results showed that the indicators used on each of these variables showed where the organizational culture was in the good category. For teacher performance indicators are in the good category. Based on the correlation test, there is a strong/high relationship between the two variables. So it can be concluded that there is a significant influence between organizational culture on teacher performance at SMK Negeri 1 Bungoro. This research can be used as a reference for future research that discusses organizational culture on teacher performance because previous research discussed more about organizational culture on principal leadership.